2014
DOI: 10.5430/wje.v4n6p54
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Behavioural Intentions of Typically Developing Adolescents towards a Hypothetical Peer with Asperger Syndrome

Abstract: This study examines the attitudes and the behavioural intentions of typically developing (TD) adolescents towards a hypothetical peer with Asperger syndrome (AS). Participants (N= 179, M age= 13.7 years) viewed two Powerpoint presentations one of a TD male target and one of a male target with AS. The target with AS was introduced either with descriptive or combined information delivered either by a hypothetical friend or by a hypothetical teacher. Attitudes and behavioural intentions were assessed by the admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
1
11
0
1
Order By: Relevance
“…For instance, Campbell et al (2004) found that TD children reported greater behavioural intentions towards a hypothetical TD target than towards a target presented with autism-related symptomatology. Similar findings were found on attitudes and behavioural intentions towards a hypothetical target presented as having Asperger syndrome (Fleva, 2014).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…For instance, Campbell et al (2004) found that TD children reported greater behavioural intentions towards a hypothetical TD target than towards a target presented with autism-related symptomatology. Similar findings were found on attitudes and behavioural intentions towards a hypothetical target presented as having Asperger syndrome (Fleva, 2014).…”
Section: Introductionsupporting
confidence: 72%
“…In particular, combined compared to descriptive information had no effect on attitudes towards people with AS in general and only a small effect on social (but not academic or recreational) behavioural intentions towards the target with AS. It can be considered that overall the present findings of educating participants about ASD are in line with Fleva (2014) and Swaim and Morgan (2001) but in contrast to Campbell et al (2004). However, it is important to keep in mind that this is the first study that examines the effect of the information provision in an imagined contact scenario.…”
Section: Findings Regarding Information Type and Participants' Gendermentioning
confidence: 64%
“…The gender was unreported for two (Mavropoulou and Sideridis 2014;Silton and Fogel 2012). Most were male (n = 8; Campbell 2007;Campbell et al 2019;Campbell et al 2004Campbell et al , 2005Fleva 2014Fleva , 2015Morton and Campbell 2008;Silton and Fogel 2012;Swaim 1998;Swaim and Morgan 2001), and there was one female (Silton and Fogel 2012). From the data reported, the mean age of unfamiliar target children was 12.71.…”
Section: Participantsmentioning
confidence: 98%
“…In contrast, participants in studies assessing stigma without a target child or towards unfamiliar peers with ASD were often those shown to be unknowing about autism (either from never having heard of autism, or an inability to provide a reasonable description/ definition) and/or in a school classroom that did not have any autistic children (Campbell et al 2004(Campbell et al , 2005Fleva 2014Fleva , 2015Morton and Campbell 2008;Scheil, Bowers-Campbell, and Campbell 2017;Silton and Fogel 2012;Swaim 1998;Swaim and Morgan 2001). In one case those classes with higher numbers of children with ASD were allocated to control conditions (Staniland and Byrne 2013).…”
Section: Participantsmentioning
confidence: 99%
“…Negativan stav može da onemogući uspostavljanje socijalne interakcije, pa posledično i da se deci sa autizmom pruži model ponašanja koji je neprihvatljiv u društvenim okolnostima. Rezultati studije koju je sprovela Fleva ukazuju da deca bolje prihvataju vršnjaka sa ometenošću ukoliko ga je predstavio drug nego nastavnik (Fleva, 2014). Zbog toga je važno da se deca tipičnog razvoja pripreme za dolazak deteta sa posebnim potrebama, i da se upoznaju sa njegovim karakteristikama i razvojnim specifičnostima.…”
Section: Uvodunclassified